Revisiting Planning Standards for Open Spaces in Urban Areas from Global and National Perspectives - Khan, Adil Mohammed (Journal of Bangladesh Institute of Planners, 2019)
Open space are regarded as an integrated part of urban areas for providing recreational benefits as well as maintaining ecological balance. However ‘how much open space should be designed for urban areas’ – have been a topic of discussion among planners and policy makers across the world over the years. Different countries have adopted various standards for designing their urban areas considering their own contexts. However, proper understanding of open space standards followed in various cities and countries around the world is quite important for development of planning standards for sustainable cities and settlement. This paper primarily focuses on open space standards followed in various cities and countries in the world as well as open space standards adopted in various plans and projects in Bangladesh. The research is based on secondary information supported by a review of literature for a better understanding of the planning standards for open space across global cities. Planning standards and provisions regarding open space facilities practiced for urban planning for various cities in Bangladesh in respective master plans, structure plans or any other relevant plans have been explored. The paper reveals that there are no universal standards for open space provisions in the urban areas. An appropriate standard for open space based on the contextual situation of an urban area may, however, guide development of required recreational facilities. It is imperative that such planning standards are followed through proper development and implementation of physical plans of cities. JBIP, Vol. 12, 2019 (Printed in June 2020), pp. 1-20